Factores que influyen en el acoso escolar y la intervención del trabajador social, en los estudiantes del noveno año de educación básica del colegio de bachillerato Beatriz Cueva De Ayora, de la ciudad de Loja, en el periodo de enero a julio de 2015 - Sánchez Reina, Eliana Elizabeth (2016)
Considering that bullying is a latent social problem in the educational context, where groups of students live day to day this situation can be clearly identified fear, fear, altering behaviors that cause them; in this perspective, addressing the research topic of bullying and its interpretation, it has been coated very important because he has permitted respond to existing social and convivial needs within educational institutions, as well as analysis of the new realities we offer modern times. In the research called "Factors influencing bullying and intervention Social Worker in students the ninth year of basic education College High School Beatriz Cueva de Ayora, the city of Loja, in the period January to July 2015 "it has been identified that bullying alter their moods and what are the places chosen for this type of violence are. The fear and dread, are indicators that force people to stay silent about the violence, understanding that even society views violence as normal, being even worse than the victim to remain silent about this problem as over time can have negative consequences, where not only will be affected individually, but this dragged his family and society in general. To tell the Ministry of Education "The contribution of Social Work from the Departments of Student Counseling is understood as the area investigating specific processes that relate to the lives of individuals, their needs and potentials. also involved in the recognition and resolution of problems between human and institutional interactions to achieve greater social welfare. Social work is concerned with improving the environment of individuals and the needs of a specific population in a given period of time with the goal of achieving greater integration "So it is necessary to visualize our intervention in educational institutions, where they play an important role, as they seek to achieve greater social welfare, dealing with each of the needs of the population, considering whether the family, community and social environment is favorable or not for their educational process. In this perspective it is necessary that each person, in this case student or teacher, or report the case come to him, without their support our intervention can not be.